Diagnosis of Invasive Amebiasis by Enzyme-Linked Immunosorbent Assay of Saliva To Detect Amebic Lectin Antigen and Anti-Lectin Immunoglobulin G Antibodies - Abd-Alla, Mohamed D. (American Society for Microbiology, 2000)
Saliva from subjects with amebic liver abscess (ALA), acute amebic colitis, asymptomatic infection with Entamoeba histolytica or Entamoeba dispar, and uninfected controls was tested by enzyme-linked immunosorbent assay (ELISA) for the presence of E. histolytica galactose-inhibitable lectin antigen and salivary immunoglobulin (IgG) antibodies to a recombinant cysteine-rich lectin-derived protein (LC3). Salivary lectin antigen was found in 65.8% of subjects with acute colitis, compared to 22.2% of those convalescent from ALA, 10.0% with asymptomatic E. histolytica infection, 9.8% with E. dispar infection, and 2.6% of controls (subjects from the United States and study patients with nonamebic diarrhea) (P < 0.001 for each compared to values for subjects with colitis). Salivary anti-LC3 IgG antibodies were found in 92% of ALA patients regardless of duration of illness and in 83.3% of colitis patients who were symptomatic for at least 7 days (P < 0.001 compared to other study groups). Serum anti-LC3 IgG antibodies were detected in 56.3% of subjects with acute colitis, 100% of subjects with ALA or prolonged colitis, 45% of subjects with asymptomatic E. histolytica infection, 32.3% of subjects with E. dispar infection, and 23.4% of diarrhea controls. In comparison to ELISA for serum anti-LC3 IgG antibodies, the salivary lectin antigen assay is a more sensitive and specific test for acute amebic colitis. Detection of salivary anti-LC3 IgG antibodies by ELISA is an effective means for the diagnosis of ALA and prolonged cases of amebic colitis.